2017
DOI: 10.1038/srep41647
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of recombinant human cytoglobin against chronic alcohol-induced liver disease in vivo and in vitro

Abstract: Alcoholic liver disease (ALD) is an important worldwide public health issue with no satisfying treatment available since now. Here we explore the effects of recombinant human cytoglobin (rhCygb) on chronic alcohol-induced liver injury and the underlying mechanisms. In vivo studies showed that rhCygb was able to ameliorate alcohol-induced liver injury, significantly reversed increased serum index (ALT, AST, TG, TC and LDL-C) and decreased serum HDL-C. Histopathology observation of the liver of rats treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
5
16
0
Order By: Relevance
“…Indeed, in a study of an alcoholic liver disease model, treatment with recombinant human Cygb significantly inhibited Kupffer cell (KC) proliferation and tumor necrosis factor-alpha (TNF-α) expression, in LPS-stimulated KCs. Cygb also inhibited LPS-induced NADPH oxidase activity and ROS, NO, and O 2 •− generation (Wen et al, 2017). In addition, Cygb-deficient mice exhibited increased inflammation (Thuy et al, 2015;Van Thuy et al, 2017), as well as increased expression of TNF-α mRNA and many genes associated with inflammation (Yassin et al, 2018).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, in a study of an alcoholic liver disease model, treatment with recombinant human Cygb significantly inhibited Kupffer cell (KC) proliferation and tumor necrosis factor-alpha (TNF-α) expression, in LPS-stimulated KCs. Cygb also inhibited LPS-induced NADPH oxidase activity and ROS, NO, and O 2 •− generation (Wen et al, 2017). In addition, Cygb-deficient mice exhibited increased inflammation (Thuy et al, 2015;Van Thuy et al, 2017), as well as increased expression of TNF-α mRNA and many genes associated with inflammation (Yassin et al, 2018).…”
Section: Introductionmentioning
confidence: 91%
“…Primary rat cultures were prepared as previously described (Soares et al, 2013). To stimulate the cells, they were incubated with LPS (Sigma-Aldrich, St. Louis, MO, USA; 10 µg/ml) or recombinant rat Cygb (Cusabio Technology, Houston, TX, USA; 10 and 20 µg/ml) for 4 h. The concentrations of LPS and Cygb used were based on previous studies (Wen et al, 2017;Leisengang et al, 2018). PBS was used as a negative control.…”
Section: Preoptic Area Primary Cell Culturesmentioning
confidence: 99%
“…[11][12][13][14] Emerging evidences indicated that Cygb is negatively associated with liver fibrosis and HCC tumorigenesis via regulating oxidative stress pathways. [15][16][17][18][19] Cygb absence accounts for a high incidence of multiple malignancies including liver, lung and colon cancer and lymphoma in aged Cygb −/− mice, compared with wide-type mice. 20,21 Its deficiency also contributes to tumor recurrence and poor prognosis in human gliomas.…”
Section: The Interaction Of Ons Withmentioning
confidence: 99%
“…It is a dynamic mediator in the maintenance of redox homeostasis and performs the activities of peroxidase and nitric oxide dioxygenase (NOD), which catalyzes nitric oxide (NO) or nitrite to nitrate in rat hepatocytes . Emerging evidences indicated that Cygb is negatively associated with liver fibrosis and HCC tumorigenesis via regulating oxidative stress pathways . Cygb absence accounts for a high incidence of multiple malignancies including liver, lung and colon cancer and lymphoma in aged Cygb −/− mice, compared with wide‐type mice .…”
Section: Introductionmentioning
confidence: 99%
“…[19] In the previously study, we found rhCygb had the e cacy of preventing atherosclerosis, protecting against chronic liver disease and liver brosis. [20][21][22][23] Therefore, in this study, we intended to investigate the e cacy of rhCygb in a lung brosis rat model induced with BLM.…”
Section: Introductionmentioning
confidence: 99%